ARTIFICIAL INTELLIGENCE IN RADIOLOGY: COMPREHENSIVE REVIEW OF AUTOMATED MRI AND CT IMAGE ANALYSIS (International journal of medical sciences, 2025)
Artificial intelligence (AI) has emerged as a transformative force in radiology, enabling automated MRI and CT interpretation with unprecedented accuracy and efficiency. This comprehensive review expands on the technical principles, deep learning models, clinical applications, workflow integration, and existing limitations associated with AI in radiological imaging. By examining multimodal datasets, segmentation architectures, evaluation strategies, and regulatory perspectives, the article provides a detailed foundation for understanding how AI systems are currently utilized in neuroradiology, thoracic imaging, stroke diagnostics, and cardiovascular imaging. The review emphasizes the need for robust validation, bias mitigation, explainable AI, and integration with PACS/RIS platforms for safe and effective clinical adoption.